Conjugate vaccines for enteric fever: proceedings of a meeting organized in New Delhi, India in 2009 - Podda, Audino; Saul, Allan James; Arora, Rashmi; Bhutta, Zulfiqar; Sinha, Anju; Gaind, Rajni; Singhal, Tanu; Saha, Samir; Brooks, Abdullah; Martin, Laura B.; Amdekar, Yeshwant; Chitkara, Amar Jeet; et al. (The Journal of Infection in Developing Countries, 2010)
Enteric fever is responsible for significant morbidity in South Asia and high prevalence of severe disease is seen in children under two years of age. Effective typhoid vaccines are available, but they cannot be used for children under two years of age and also have some limitations in older age groups. Participants supported development of a Salmonella Typhi conjugate vaccine able to induce effective, long-lasting immunity in young children. The role of Salmonella Paratyphi A as a cause of enteric fever was discussed and consensus reached that a bivalent S. Typhi-S. Paratyphi A conjugate vaccine is highly desirable; however, considering disease epidemiology and the advanced status of vaccine development, rapid introduction of monovalent S. Typhi conjugate vaccine into vaccination programs of South Asia was recommended. Prevention should be emphasized, available vaccines used, and efforts toward improving sanitation continued. Success of the new vaccine will depend on several factors, including delivery costs and governmental ability to adopt and implement suitable immunization programs. To ensure good immunization coverage, the conjugate vaccine could be administered either to young infants, concomitantly with infant EPI vaccines, or to older infants, concomitantly with measles vaccine, currently given at 9 to 12 months. The need for new combination vaccines, containing both EPI and typhoid antigens, was discussed as a tool to increase coverage and reduce the number of injections and priority conflicts in a crowded infant vaccination schedule. However, stand-alone enteric fever conjugate vaccines would allow more flexibility to immunize different age groups and therefore should be rapidly developed.